Antibacterial Test of Keji Beling Leaf Starch Extract (Strobilanthes crispus) Against Inhibition Zone Salmonella thypi - Ayu Putri Ariani; Yuli Febrianti; Mareta Widiya (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
Salmonella typhi is a gram-negative rod-shaped bacterium, which can cause typhoid fever. Keji Beling (Strobilanthes crispus) is a medicinal plant that contains metabolic substances such as flavonoids that function as antibacterial. The aim of this research was to determine the antibacterial activity of the starch from the leaves of the Keji Beling (Strobilanthes crispus) against the inhibition zone of Salmonella thypi. This study consisted of an experimental study with a completely randomized design (CRD). One Way Anova statistical test results obtained sig. ie 0.99 0.05, which means the results were not significant. The conclusion in this study was that the concentration of starch from the leaves of Keji Beling (Strobilanthes crispus) had no effect on the inhibition zone of Salmonella thypi.